Pengaruh Terapi Oksigen Hiperbarik terhadap Kadar Testosteron pada Tikus Model Sindroma Ovarium Polikistik dengan Resistensi Insulin - Fajar Sudiono; Lunardhi Susanto; Wachjudi Kurnia (Universitas Hang Tuah, 2021)
Background:Polycystic ovary syndrome (PCOS) is an endocrine disorder that has the broadest and best in women often springs reproduktif age. Factors underlying the recovery of PCOS are excessive androgens, insulin resistance, and disturbance of gonadotropin dynamics. Excessive androgen causes LH and FSH to develop. In the theory hyperbaric oxygen therapy allows to increase sensitivity tissue to insulin. The . The purpose of this research was to know effect using hyperbaric oxygen therapy 2.4 ATA 3x30 minutes for 5 sessions on testosterone levels on rats model of Polycystic Ovary Syndrome with insulin resistance.Metode:The research is experimental with post test only control group design. The total sample used as 12 rats that is divided into 2 groups. Independent variable is therapeutic oxygen hiperbarik, dependent variable testosteron level from blood sample of rats and control variables are room temperature and standard feed and control variables of androgen injection, types and specifications of experimental animals, cage size and animal care. Data analysis of this study was processed using Mann Whitney U test.Result:The results of using Mann Whitney U Test with p-value = 0,150 > α (0.05), showed no difference between testosterone levels in the experimental group given androgen injection with the group of animals given androgen injection and hyperbaric oxygen therapy.Conclusion:Therapy oxygen hyperbarik has not been effecting testosteron levels in white rats (Rattus Norvegicus) model syndroma ovarium polycystic with resistensi insulin